Mothering and desistance in re-entry - Michalsen, Venezia, 1976- (Abingdon, Oxon : Routledge, 2019)
Although there is plentiful research on the impact of marriage, employment and the military on desistance from criminal behaviour in the lives of men, far less is known about the factors most important to women's desistance. Imprisoned women are far more likely than their male counterparts to be the primary caretakers of children before their incarceration, and are far more likely to intend to reunify with their children upon their release from incarceration. This book focuses on the role of mothering in women's desistance from criminal behaviour. Drawing on original research, this book explores the nature of mothering during incarceration, how mothers maintain a relationship with their children from behind bars and the ways in which mothering makes desistance more or less likely after incarceration. It outlines the ways in which race, gender, class, nationality, sexuality, gender identity, and other characteristics affect mothering and desistance, and explores the tensions between individual and system-level factors in the consideration of desistance. This book suggests that any discussion of desistance, particularly for women, must move beyond the traditional focus on individual characteristics and decision-making. Such a focus overlooks the role played by context and systems which undermine both women's attempts to be mothers and their attempts to desist. By contrast, in the tradition of Beth Richie's Compelled to Crime, this book explores both the trees and the forests, and the quantum in-between, in a way that aims for lasting societal and individual changes.
Mothering and desistance: introduction -- Incarcerated women and mothers around the world -- Methods and theory -- Women and mothers coming home -- Mothering, desistance, and redemption -- The way forward.
OCLC-licensed vendor bibliographic record.
Keywords: Female offenders -- Rehabilitation; Criminals -- Rehabilitation; Motherhood; SOCIAL SCIENCE / Penology; SOCIAL SCIENCE / Criminology